Development of a Hypercontent Book for the Program Evaluation Course in Educational Technology - Mulyadi; Widyaningrum, Retno; Ardiansyah, Acep Ahmad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study aimed to develop and validate a hypercontent book as an innovative learning resource for the Program Evaluation course in the Educational Technology Study Program at Universitas Negeri Jakarta. The study was motivated by the limited availability of engaging and multimedia-rich learning materials that support students’ independent learning in higher education. A design and development approach was employed using Rowntree’s instructional design model, which comprises three stages: planning, preparation for writing, and writing and editing. A needs analysis was first conducted to identify students’ learning needs and course characteristics, which then informed the integration of text, audio, visuals, and video into an interactive hypercontent format. The developed product was evaluated through expert review involving subject-matter, media, and instructional design experts, as well as a one-to-one evaluation with three students. The expert appraisal showed high levels of validity and feasibility, with average scores of 4.5 out of 5 for content accuracy, 4.7 for multimedia integration, and 4.6 for usability, while the student evaluation yielded an average score of 4.67 out of 5. These findings indicate that the hypercontent book is pedagogically appropriate, technically feasible, and supportive of self-paced learning. The study concludes that hypercontent-based instructional materials can enhance learner engagement and enrich learning experiences in specialized higher education courses. This research contributes to the growing literature on digital learning resource development by demonstrating the potential of hypercontent books as interactive and scalable tools for course-specific instruction in higher education.